Stimuli-responsive hydrogels, their mass transfer, intermolecular interactions, and applications in biomedical devices - Parker M. Toews; Ashwin Velraj; Jeffrey S. Bates (Journal of Materials Science: Materials in Engineering)
Abstract Hydrogels are versatile materials that can be used in biomedical applications, where their multifunctional capabilities can be leveraged as sensors, actuators, drug delivery devices, and chemomechanically responsive materials. This review article explores the diverse applications of hydrogels and their chemomechanical response. The foundations of hydrogels, encompassing their physics, chemistry, and diffusion properties, are presented, providing a comprehensive understanding of their behavior. Synthesis and fabrication challenges, such as batch consistency, storage stability, degradation, and inconsistent mechanical swelling behavior, are addressed. Hydrogels are often characterized by using a variety of methods to define the full scope of their material properties, including structural analysis, UV–visible spectroscopy, dynamic mechanical analysis, scanning electron microscopy, rheology, optical microscopy, pressure sensing, and nuclear magnetic resonance. The current state of the art of hydrogels is explored, focusing on the physical and chemical properties and some theories and mathematical models that describe their behavior. We discuss drug delivery, diffusion studies, controlled release, sustained drug interactions, and various drug delivery methods, ranging from transdermal to ocular to mucous membranes. We further present hydrogels as viable candidates for 3D-printed devices, including sensors and actuators, where we examine specificity, selectivity, biomarker interactions, and molecularly imprinted polymers. The emerging areas of 3D-printed hydrogel devices, microfluidics, and soft robotics and their potential uses are highlighted. Finally, limitations, opportunities, and future research directions are proposed to enhance commercial viability and define potentially valuable insights for future advancements in the field.